High Prevalence of Radiological Vertebral Fractures in Patients With TSH-Secreting Pituitary Adenoma - Frara, Stefano (J Endocr Soc, 2018)
BACKGROUND: Bone loss and high risk of fractures have been reported in patients with primary hyperthyroidism, whereas data on skeletal health in TSH-secreting adenoma (TSH-oma) are scant, and the risk of fractures in this specific clinical context has not been investigated so far. In this cross-sectional study, we aimed at evaluating for the first time, to our knowledge, the prevalence and determinants of radiological vertebral fractures (VFs) in patients with TSH-oma. METHODS: Twenty-two patients (10 males, 12 females; median age 47 years) with TSH-oma and 44 patients (20 males, 24 females; median age 49 years) with nonfunctioning pituitary adenoma (NFPA) were retrospectively evaluated for thoracic VFs using a morphometric approach on lateral chest X-ray routinely performed in the presurgical diagnostic workup. RESULTS: The prevalence of VFs was significantly higher in TSH-oma vs NFPA (59.1% vs 22.7%; P = 0.003), the difference being still significant (odds ratio, 10.5; P = 0.005) after correction for the size of pituitary adenomas and biochemical parameters. In TSH-oma, the prevalence of VFs was significantly associated with older age (P = 0.007) and higher serum free T4 values (P = 0.02). In 20 patients, data on presurgical medical therapies of TSH-oma were available. All patients not treated with somatostatin receptor ligands were fractured compared with 25% of those who were treated with these drugs (P = 0.001). No significant (P = 0.25) association between VFs and treatment with methimazole was found. CONCLUSIONS: This study provides the first evidence, to our knowledge, that patients with TSH-oma may develop VFs in close relationship with severity of hyperthyroidism.